THE EFFECTIVENESS OF SUPPLEMENTAL EXERCISES TEXTBOOK ON COMPREHENDING MORPHEMES - Rayanto, Yudi Hari (FKIP Universitas Islam Jember, 2019)
This research is taken during the researcher has subjects of Morphology in the classroom. This research aims to find out whether supplemental exercises textbook is effective to be implemented on comprehending morpheme as well as gaining high achievement on learning morphology. All data were collected through a questionnaire and tests are given to twenty-five college students. Of twenty-five students, two students did not join the exercise, but in the final test, twenty-four students took part in the final exam. All data gained were analyzed by using descriptive quantitative study. The result shows that the supplemental exercises textbook was effective to be implemented. It can be seen from the result of a questionnaire which can be called a high category level. Further, the result of students’ learning achievement was 83%. It means that students have improved their learning achievements. Keywords: Morpheme, Supplemental, Word Power